Aplicación móvil para la georeferenciación de buses urbanos en la ciudad de Loja. - Loayza Abad, Freddy Patricio (2016)
This thesis project is the analysis, design and implementation of a mobile application for georeferencing of urban buses in the city of Loja Android operating system, which is aimed at any type of user you want to interact with an application easily use with friendly and intuitive interfaces. One of the highlights of this work is the synchronization mechanism of two databases (one located on a remote server and the other on the mobile device), which allows the possibility of displaying information without internet connection. The methodology used to develop the application is mobile-d, which is an agile software methodology. Mobile-D is based on extreme programming (XP) for implementation, methodologies glass scalability and Unified Development Process RUP coverage lifecycle. Mobile-D consists of 5 phases such as: Exploration, Initialization, Production, Testing and System Stabilization. Using the methodology, procedures and techniques used for the development of the thesis project has allowed meet the objectives for the development of mobile application that allows visualization of urban buses from the city of Loja in real time.